The Theory of Postcolonial Trauma and its Impact on the Religious Studies - Yan Okhtavianus Kalampung (Potret Pemikiran, 2021)
This article argues that postcolonial trauma theory is beneficial not only for recognizing postcolonial people’s trauma but also for the development of religious studies. The western trauma theory ignored the trauma of colonialism which still has many influences in the contemporary world. Here to respond to that condition, the postcolonial trauma theory shall probe how colonialism left trauma in the society of postcolonial people. Not only that topic, but this article also investigates how the adaptation of postcolonial trauma theory on religious studies. Because religion, as a fact of contemporary society, has got a thorough influence from colonialism. The approach of this study is qualitative research by investigating literature about postcolonial trauma. By probing the literature around the postcolonial trauma theory and its adaption in religious studies, this article shall open the possibility of another development in religious studies. This research concludes that the postcolonial trauma theory can be advantageous to religious studies. Keywords: Postcolonial trauma; trauma studies; religious studies; biblical studies.